SYSTEMATIC LITERATURE REVIEW: PENGELOLAAN KELAS YANG EFEKTIF DENGAN MENGGUNAKAN COOPERATIVE LEARNING - Siti Nurhalijah Nasution,; Tria Tansa Audina,; Khodijah, Khodijah; Arita Marini, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
Abstract: Today, education has become a basic need for every individual. In Indonesia, the government makes a policy for every citizen to be able to get the right to education for 12 years and is advised more than that. Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation and state.